Exploring the Nexus between Internal Control Structures and Good Corporate Governance - Ahmad, Hamzah; Muslim, Muslim (Advances in Applied Accounting Research, 2024)
Purpose: This study examines the impact of internal control effectiveness on organizational performance, with a focus on the mediating role of governance mechanisms. It aims to explore how internal controls contribute to transparency, accountability, and overall quality of governance. Research Design and Methodology: The study employs a mixed-method approach, combining empirical analysis and theoretical perspectives from corporate governance and organizational behavior. Data were collected through a literature review, case studies, and statistical analysis of financial performance metrics to assess the relationship between internal controls and governance outcomes. Findings and Discussion: The results indicate a positive correlation between internal control effectiveness and financial reporting quality. Strong control mechanisms enhance transparency and accountability, while governance elements such as board oversight, organizational culture, and stakeholder engagement influence internal control practices. The study also finds that internal controls mediate the relationship between governance mechanisms and organizational performance, reinforcing the link between governance, risk management, and performance. Implications: The findings suggest that organizations should prioritize board composition, independence, and expertise while fostering a culture of integrity and accountability. These insights contribute to the field of corporate governance research and underscore the importance of interdisciplinary approaches. Future studies should explore industry-specific governance challenges and the role of technology in internal control systems.